Microalgae gasification over Ni loaded perovskites for enhanced biohydrogen generation. (March 2023) - Valizadeh, Soheil; Khani, Yasin; Farooq, Abid; Kumar, Gopalakrishnan; Show, Pau Loke; Chen, Wei-Hsin; Lee, See Hoon; Park, Young-Kwon
Highlights: The steam gasification of microalgae was carried out to obtain H2 -rich gas. Ni-perovskite oxide catalysts showed a high catalytic effect toward H2 generation. The synergetic effect of metallic Ni and perovskite elements was observed. The elevating temperature was conducive to enhancing gas yield and H2 selectivity. Abstract: Steam gasification of microalgae upon perovskite oxide-supported nickel (Ni) catalysts was carried out for H2 -rich gas production. Ni-perovskite oxide catalysts with partial substitution of B in perovskite structures (Ni/CaZrO3, Ni/Ca(Zr0.8 Ti0.2 )O3, and Ni/Ca(Zr0.6 Ti0.4 )O3 ) were synthesized and compared with those of the Ni/Al2 O3 catalyst. The perovskite oxide supports improved Ni dispersion by reducing the particle size and strengthening the Ni-support interaction. Higher gas yields and H2 selectivity were obtained using Ni-perovskite oxide catalysts rather than Ni/Al2 O3 . In particular, Ni/Ca(Zr0.8 Ti0.2 )O3 showed the highest activity and selectivity for H2 production because of the synergetic effect of metallic Ni and elements present in the perovskite structures caused by high catalytic activity coupled with enhanced oxygen mobility. Moreover, increasing the temperature promoted the yield of gas and H2 content. Overall, considering the outstanding advantages of perovskite oxides as supports for Ni catalysts is a promising prospect for H2 production via gasification technology.